Digital twin production in the architecture, engineering, construction and operation industry: Organizational attributes and strategies - Yuveelai Bunjaridh, Nop; Abdul Rahimi, Abdul Rahman; Liyana, Mohamed Yusof (Engineering Project and Production Management, 2023)
Digital twin technology has grown over the years. However, a digital twin cannot be produced effectively without adequate organizational attributes. Inaccurate digital twins cannot be used for the operation and maintenance phase. Thus, an effective digital twin reduces waste resources in the operation and maintenance phase. The primary objective of this study is to identify the attributes to produce a digital twin in their building projects. In achieving the objective, interview data with 20 industry professionals involved with the digital twin was collected and analyzed. With the readiness assessment tool developed, relevant strategies can be implemented to correspond to the tool and allow for an improved future state in managing the construction industry. A total of three main categories and six subcategories were identified. The study findings can be used to develop organizational attributes and strategies required to produce a digital twin.